Tax and Fee Instruments for Biodiversity Conservation: International Review and Implications for Vietnam - Van Manh, Lai; Thi Hue, Hoang; Van Hieu, Nguyen (VNU Journal of Science: Policy and Management Studies; Vol 41 No 3DO - 10.25073/2588-1116/vnupam.4556, 2025)
The global decline of biodiversity has prompted many countries to implement tax and fee instruments such as environmental taxes, ecosystem service fees, ecological credits, conservation bonds, and payments for ecosystem services (PES) to support sustainable conservation efforts. This study was conducted with the objective of providing an overview of international practices regarding tax and fee instruments in biodiversity conservation, thereby drawing key implications that may serve as references for Vietnam. Based on an analysis of practical experiences from 22 countries, improving tax and fee policies to internalize environmental costs, mobilize sustainable financing, and incentivize eco-friendly behaviors is of critical importance. Accordingly, seven key lessons are recommended related to: i) Designing taxes and fees based on ecological value and behavioral incentives; ii) Reinvesting revenues through dedicated conservation funds; iii) Adapting instruments to institutional capacities; iv) Integrating taxes and fees into green development strategies; v) Ensuring social equity and community participation; vi) Applying digital technology and communication to build consensus; and vii) linking domestic mechanisms with the global biodiversity finance ecosystem. These recommendations aim to establish a more transparent, equitable, and effective financial mechanism for biodiversity conservation in Vietnam, thereby contributing to the achievement of international commitments and sustainable development goals.